Pengembangan Media Kartu Domino Modifikasi Pada Pembelajaran Tematik di Sekolah Dasar - Zaeni, Abu; Ngainun Na’ima, Alfin (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2025)
This research develops a modified domino card learning media as a new innovation to enhance students' understanding in Thematic learning for Grade III at SDN Kebonrejo 1 Kepung Kediri, specifically Theme 8 "Praja Muda Karana" Subtheme 2 "Aku Anak Mandiri" Lessons 5 and 6. This research offers novelty by integrating game elements based on modified domino cards specifically designed to support more interactive and engaging thematic learning. The development model used is ADDIE, consisting of five stages: Analysis, Design, Development, Implementation, and Evaluation. Data were collected through interviews, observations, questionnaires, and tests (pretest and posttest). Data analysis methods involved qualitative and quantitative analysis. Qualitative data were obtained through interviews and observations, which were analyzed to understand the learning context and validator feedback. Quantitative data were analyzed using Microsoft Excel and SPSS 29 to process the results of media validation, questionnaires, and pretest and posttest comparisons. Instrument validity was tested using Product Moment correlation, while questionnaire reliability was calculated using Cronbach's Alpha, with reliability values above 0.7 indicating adequate instrument consistency. The effectiveness test was carried out through N-Gain Score analysis, showing an increase in student learning outcomes from 46 to 88 with an N-Gain value of 78% (effective category). The practical implications of this research include the application of learning media that not only improves student learning outcomes but also creates a more enjoyable and interactive learning atmosphere. This media provides an alternative for teachers to overcome the limitations of conventional methods such as lectures and question-and-answer sessions. With an easy-to-use design, this media can be adopted by teachers in various schools for thematic learning and other relevant subjects.